PERAN MEDIASI TRUST TERHADAP KEPUTUSAN MEMBUKA REKENING BANK DIGITAL PADA GEN Z - maharany, indah dewi; Nurul Husna, Habsyi; Azfa Hani, Aulia; Musyafak, Ali (Jurnal Bisnis dan Kewirausahaan, 2023)
This research aims to determine the influence of independent variables, namely knowledge, user interface and ease on the dependent variable, namely the decision of Gen Z in Kudus district to open a digital bank account through trust as an intervening variable. The research method used in this research is a quantitative method with an associative approach. Data collection was carried out through a Google Form questionnaire which was distributed to digital banking users from Gen Z in Kudus Regency. A total of 100 questionnaires were used and analyzed using the Partial Least Square-Structural Equation Model (PLS-SEM). The findings in this research show that ease and trust have a positive influence on generation Z's decision to open a digital bank account in Kudus Regency. However, on the contrary, knowledge and user interface actually weaken the level of Gen Z's decision to open a digital bank account. Furthermore, knowledge and user interface have a significant effect on Gen Z's trust in opening a digital bank account in Kudus Regency and conversely, ease has no effect on Gen Z's trust in Kudus Regency in opening a digital bank account. Apart from that, trust is able to mediate knowledge and user interface in customer decisions in opening a digital bank account. On the other hand, trust is unable to mediate ease in customers' decisions in opening digital bank accounts.